"I don't think the problem's the student…I think it's us": Engaging faculty in curriculum innovation. Issue 4 (27th November 2020) - Kornegay, Elizabeth C.; Jackson, Tate H.; LaGarry‐Cahoon, Alison; Reside, Jonathan M.; Wolcott, Michael D.; Quinonez, Rocio B.
Abstract: Purpose: The need to innovate predoctoral dental education is well established; however, there are few recent reports to guide substantial curriculum transformation. The purpose of this study was to describe faculty perspectives on their vision of future graduates, curriculum needs, and potential barriers to a successful redesign. This information would be used to inform strategic planning for the predoctoral curriculum transformation. Methods: Eighty full‐time faculty from the University of North Carolina Adams School of Dentistry participated in 60‐minute focus groups in March 2018. Focus group questions were developed to elicit perceptions about the current curriculum, what the dental graduate should know in 2040, and what is needed to engage faculty in curriculum change. Transcripts of the focus group sessions were analyzed by a third‐party research group using qualitative thematic analysis to identify pertinent themes shared by participants. Results: Faculty identified that developing clinical skill that engages multiple specialties, student time to engage in advocacy activities, and opportunities to integrate biomedical, clinical, and behavioral sciences as critical features of the curriculum. They believed the 2040 graduate should be able to critically evaluate literature, exhibit strong leadership skills, and adapt to the changing healthcare environment. To better engage faculty in curriculum change, there needs to be dedicated time, sufficient resources, a clear plan, and greater collaboration across the school. Conclusion: When embarking on curriculum transformation, engagement with faculty is a critical component of the change process. Focus groups can be used as a technique to better understand faculty perspectives about curricular needs and the overall vision.